The Francis Chan collection - Chan, Francis, 1967-; Yankoski, Danae; Sprinkle, Preston M., 1976-; Beuving, Mark (Colorado Springs, CO : David C. Cook, 2013)
Now available! All four of Francis Chan's New York Times bestselling books in one edition!
Crazy love -- Forgotten God -- Erasing hell -- Multiply.
Online resource; title from READ title page (Overdrive, viewed January 27, 2015)
Includes bibliographical references.
Keywords: Christian life; Spiritual life -- Christianity; Hell -- Biblical teaching; Future life; Discipling (Christianity); Christian life; Discipling (Christianity); Future life; Hell -- Biblical teaching; Spiritual life -- Christianity; RELIGION / Christian Life / General; Electronic books; Electronic books